APLIKASI INOKULAN AZOSPIRILLUM SP. DAN FMA PADA TANAMAN JAGUNG YANG TERCEKAM KEKERINGAN TERHADAP N, P, K TANAH - Kandowangko, Novri Y. (Sainstek, 2009)
A research was conducted to study total nitrogen, available phosphorus in soil and K-dd of soil under drought stress condition during tasseling until seed filling periods to inoculation with Azospirillum sp. and arbuscular mycorrhizal fungi (AMF) on Inceptisols. Two experiments were carried out in green house, using randomized block design arranged in factorial pattern. In pot experiment, two factors were assigned, i.e. inoculation with Azospirillum(0, 0.5, 1.0, 1.5 mL pot-1) and inoculation AMF (0, 12.5, 25.0, 37.50 g pot-1). Results of experiments showed that application AMF and Azospirillum sp. on certain dosage increased total nitrogen and available P of soil. However, inoculation Azospirillum, sp. and FMA didnt effect to K-dd of soil.